Doxycycline PEP can induce doxycycline resistance in Klebsiella pneumoniae in a Galleria mellonella model of PEP - Kenyon, Chris; Gestels, Zina; Vanbaelen, Thibaut; Abdellati, Said; Van Den Bossche, Dorien; De Baetselier, Irith; Xavier, Basil Britto; Manoharan-Basil, Sheeba Santhini (Frontiers in Microbiology, 2023)
Abstract Background Four randomized controlled trials have now established that doxycycline post exposure (sex) prophylaxis (PEP) can reduce the incidence of chlamydia and syphilis in men who have sex with men. These studies have concluded that the risk of selecting for antimicrobial resistance is low. We evaluated this risk in vitro and in vivo using a Galleria mellonella infection model. Methods We evaluated how long it took for doxycycline resistance to emerge during passage on doxycycline containing agar plates in 4 species – Escherichia coli, Klebsiella pneumoniae, Neisseria gonorrhoeae and Neisseria subflava. We then assessed if K. pneumoniae could acquire resistance to doxycycline (and cross resistance to other antimicrobials) during intermittent exposure to doxycycline in a Galleria mellonella model of doxycycline PEP. Results In our passage experiments, we found that resistance first emerged in K. pneumoniae. By day 7 the K. pneumoniae MIC had increased from 2 mg/L to a median of 96 mg/L (IQR 64-96). Under various simulations of doxycycline PEP in the G. mellonella model, the doxycycline MIC of K. pneumoniae increased from 2 mg/L to 48 mg/L (IQR 48-84). Ceftriaxone and ciprofloxacin MICs increased over ten-fold. Whole genome sequencing revealed acquired mutations in ramR which regulates the expression of the AcrAB-TolC efflux pump. Conclusion Doxycycline PEP can select for doxycycline, ceftriaxone and ciprofloxacin resistance in K. pneumoniae in a G. mellonella model. The emergent ramR mutations were similar to those seen in circulating strains of K. pneumoniae. These findings suggest that we need to assess the effect of doxycycline PEP on resistance induction on a broader range of bacterial species than has hitherto been the case.